Motores a relutância variável 6x4 e 6x6. Estudo comparativo de operação e desempenho - Dias, Renato Jayme (2012)
The comparative study of electric machines has been in vogue due to the growing demand for electromechanical converters with maximum possible efficiency. In this scene, the switched reluctance machines have proven to be competitive. Comparative studies between these machines and the already established induction machines can be easily found in the scientific literature, but studies on various configurations of the switched reluctance machines are not as widespread. This work shows the modeling, simulation and presents a comparative study of two Switched Reluctance Machines to a single phase (6x6) and three-phase (6x4). Aspects of construction, drive and efficiency are discussed in order to find advantages and disadvantages to each of these machines.